COLOR AND ITS SYMBOLIC MEANING IN UZBEK AND SPANISH PROVERBS: AN INTERDISCIPLINARY VIEW (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Color plays a crucial role in shaping the national worldview, reflecting the cultural, historical, and social characteristics of each nation. This article presents a comparative analysis of the symbolism of color in the Uzbek and Spanish languages. It explores the differences and similarities in the perception of key colors such as white, black, red, green, and blue in the context of proverbs, idiomatic expressions, and other linguistic-cultural elements. The article also considers the influence of religious traditions and natural conditions on color perception in both cultures. The results demonstrate that colors, as part of the linguistic and cultural code, play a significant role in reflecting national values and worldview.